A PENGARUH PEMBELAJARAN KEWIRAUSAHAAN TERHADAP NIAT BERWIRAUSAHA SISWA KELAS 11 BISNIS DIGITAL SMKN 1 SOOKO - Wilujeng, Yunda sekar; Marlena, Novi (Program Studi Pendidikan Tata Niaga Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2025)
Entrepreneurial intention is the beginning of the creation of entrepreneurial activities, and in the process of creating entrepreneurial activities, external assistance is needed to support the creation of a business. This assistance can be in the form of entrepreneurial learning. This study aims to analyze the effect of entrepreneurial learning on the entrepreneurial intention of grade 11 digital business students of SMKN 1 Sooko. This study uses a quantitative method. The location of the study was at SMKN 1 Sooko, with grade 11 digital business students as the research population. Samples were taken from grade 11 students majoring in digital business 1 and 2. The research instrument used was a questionnaire with data analysis techniques using SPSS version 25. The results showed that entrepreneurial learning influenced the entrepreneurial intention of grade 11 digital business students.